Value Investment Analysis of Engineering and Construction Companies in the United States: A Case Study of KBR - Miao Yichen (SHS Web of Conferences, 2025)
With global warming and increasing emphasis on environmental protection and sustainable development, engineering and construction companies face significant transformation and challenges. This study builds a value-investment-based comprehensive assessment framework with financial and non-financial indicators. Using KBR as a case study, the research examines financial data and non-financial information from 2020 to 2024. Quantitative and qualitative methods are applied to evaluate KBR’s competitive advantages in sustainable and digital eras. The results show that KBR possesses strong value investment potential. Financially, the company demonstrates solid solvency, efficient operational capacity, and promising growth potential, despite short-term earnings volatility. Non-financially, KBR is recognized as an industry leader in employee satisfaction, sustainable practices, and corporate governance, though brand recognition lags. The study further analyzes risk factors such as dependence on key customers, climate-related uncertainties, and earnings fluctuations. Investment recommendations suggest that long-term investors may benefit from KBR’s stable outlook, while short-term investors are advised to monitor market timing and external conditions carefully. Overall, this research provides insights that support the use of an integrated assessment framework and offers practical guidance for investors considering exposure to the engineering and construction sector.